2013
DOI: 10.1111/aogs.12213
|View full text |Cite
|
Sign up to set email alerts
|

Variation in cesarean section rates is not related to maternal and neonatal outcomes

Abstract: The rates of cesarean section, maternal complications and neonatal asphyxia vary markedly between different delivery units. Good maternal and neonatal outcomes can be achieved with cesarean section rates <15%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…In NSW between 2009 and 2010, 28.1% of nulliparous women with a singleton cephalic infant at term had a CS. Consistent with other studies, we found unexplained variation in hospital CS rates among nulliparous women at term after adjusting for differences in case‐mix. After adjusting for differences in case‐mix, labour and delivery, and hospital factors, for women who had a prelabour CS and those who had an intrapartum CS following spontaneous labour, variations in hospital CS rates were substantially reduced by 78 and 52%, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In NSW between 2009 and 2010, 28.1% of nulliparous women with a singleton cephalic infant at term had a CS. Consistent with other studies, we found unexplained variation in hospital CS rates among nulliparous women at term after adjusting for differences in case‐mix. After adjusting for differences in case‐mix, labour and delivery, and hospital factors, for women who had a prelabour CS and those who had an intrapartum CS following spontaneous labour, variations in hospital CS rates were substantially reduced by 78 and 52%, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…The appropriateness of any CS rate can only be interpreted if the attendant morbidity and mortality are known. Previous studies have found conflicting associations between overall case‐mix adjusted hospital CS rates and maternal and neonatal outcomes, with some studies finding that neonatal morbidity increased with both high and low case‐mix adjusted CS rates and others finding no association between neonatal morbidity and case‐mix adjusted CS rates . This may be due to the reporting of different neonatal outcomes (for example, 5‐min Apgar score <7 or neonatal asphyxia) for the overall case‐mix adjusted hospital CS rate.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This is consistent with findings from other studies in the USA and European countries showing no benefit of excessive obstetric interventions (e.g. caesarean delivery) in improving maternal or perinatal outcomes . The American College of Obstetricians and Gynecologists also highlighted ‘limited or uncertain benefit’ of many common obstetric practices (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…Differences in case mix have been suggested as a potential reason for these variations. Case‐mix‐adjusted variations in CS rate for a number of different countries have been presented but no such comparisons between hospitals in Sweden have previously been published. Furthermore, few previous studies have included both administrative data and medical record data as well as sociodemographic information in case mix adjustment.…”
Section: Introductionmentioning
confidence: 99%